Konstrak Keterampilan Mengajar Mahasiswa Program Pendidikan Guru Sekolah Dasar - Rustam -- (Jurnal Pendidikan dan Kebudayaan, 2015)
This research aimed to determine the construct of the teaching skills of the students of Primary School Teacher Education Program. The method used in this research was a survey. The sample of this research was taken through proportionale random sampling technique with a sample size of 640 students Primary School Teacher Education Program Open University during their teaching in the real teaching at primary schools. The data were collected by using an observation method. The data were analyzed using the applications Confirmatory Factor Analysis (CFA). The results of this research showed that the construct of the teaching skills were developed through the lesson plan, conducting the learning activities, creating the classroom climate, demonstrating mastery learning materials, conducting assessment, and reflection. In conclusion, the six factors are empirically proven to be accurately, consistently, and precisely to measure the construct of teaching skills of primary school teacher education program students.ABSTRAK Tujuan penelitian ini adalah menentukan konstrak keterampilan mengajar mahasiswa Program Pendidikan Guru Sekolah Dasar. Metode penelitian yang digunakan adalah metode Survei. Sampel penelitian diambil melalui teknik proportionale random sampling sebesar 640 mahasiswa Pendidikan Guru Sekolah Dasar Universitas Terbuka yang mengajar di kelas nyata di sekolah dasar. Pengumpulan data menggunakan metode observasi. Data dianalisis menggunakan aplikasi Analisis Faktor Konfirmatori (AFK). Hasil penelitian ini menunjukkan bahwa konstrak keterampilan mengajar dibentuk oleh perencanaan pembelajaran, mengelola kegiatan pembelajaran, mengelola iklim kelas, mendemonstrasikan penguasaan materi pembelajaran, melakukan asesmen, dan melakukan refleksi. Kajian ini menyimpulkan bahwa keenam faktor tersebut secara empiris terbukti akurat, konsisten dan memiliki ketepatan dalam mengukur konstra keterampilan mengajar mahasiswa program PGSD.